Reduce, Reuse, or Refuse? Pioneering Sustainability in the Theatre Scene in Latvia - Balcare , Kitija (Nordic Theatre Studies, 2023)
Taking into account that the performing arts could play a huge role in shaping the ecological awareness of society, it is important not only to look at the econarratives of performances but also to analyse the process of their production in terms of sustainability. Reduce, reuse, and recycle – these are essential components of environmentally responsible consumer behaviour. But what about the theatre scene? What are the main challenges for theatre professionals in terms of their ecological footprint? Despite the fact that theatre has been perceived as anti-ecological per se, the first signs of a shift in the mindset of theatre makers is already visible. There has been an increase in ecotheatre performances that not only use ecodramaturgy and represent crucial econarratives pertaining to environmental conservation but also apply aspects of sustainability in the production process of the performances. Such aspects are important in regard to the conviction that ecotheatre is becoming a form of environmental activism. During the recent pandemic (2020–22), several performances in Latvia were based on ecodramaturgy and contained features of ecotheatre. This paper aims to explore the latest sustainable practices and ecological aspects in the theatre scene in Latvia.